Desenvolvimento de nanocápsulas contendo ditranol e sua incorporação em formulação semissólida de base aquosa - Savian, Ana Luiza (2012)
Dithranol is very effective drug for the topical treatment of psoriasis. However, it has some adverse effects, such as irritation and stain in the skin that difficult its application and patient adherence to treatment. Its instability to light, high pH values, metals and the presence of oxygen, configure as a limiting step for use. So, the inclusion of drug in nanocarriers was the main objective of this work. Lipid core nanocapsules and nanoemulsions containing 0.5 mg/mL of dithranol and 0.05% of EDTA or 0.02% of ascorbic acid were prepared by interfacial deposition of preformed polymer and spontaneous emulsification methods, respectively, and evaluated in relation to its physicochemical characteristics (drug content, encapsulation efficiency, pH, mean size, polydispersity index and zeta potential). The nanocapsules, after preparation, showed satisfactory characteristics: drug content near to the theoretical concentration, encapsulation efficiency about 100%, nanometric mean size (220- 250 nm), polydispersity index below 0.25, negative zeta potential, and pH values from 5.6 to 4.4. Instead, low drug content was verified for the nanoemulsions (approximately 80%) after preparation. In photodegradation study against UVA light it was observed a higher stability of the dithranol-loaded nanocapsules comparing to solution containing the free drug (t1/2 = 4 and 1 h for nanocapsule and free drug solution containing EDTA, respectively; t1/2 = 17 and 7,5 h for nanocapsule and free drug solution containing ascorbic acid, respectively). Irritation test by HET-CAM method was conducted to evaluate the safety of the formulations. From the results it was found that nanoencapsulation of the drug decreased its toxicity compared to the effects observed for free drug. Subsequently, hydrogels containing nanocapsules were prepared employing Carbopol® 940 and Aristoflex® AVC as gel-forming polymers. The semisolid formulations showed suitable properties for topical application and higher stability when compared to nanocapsules suspensions and the hydrogel containing the free drug. Furthermore, a higher stability of dithranol was verified for hydrogels prepared with Aristoflex® AVC.